Volume-weighted Bellman error method for adaptive meshing in approximate dynamic programming - Leopoldo Armesto; Antonio Sala (Revista Iberoamericana de Automática e Informática Industrial RIAI, 2021)
Optimal control and reinforcement learning have an associate “value function” which must be suitably approximated. Value function approximation problems usually have different precision requirements in different regions of the state space. An uniform gridding wastes resources in regions in which the value function is smooth, and, on the other hand, has not enough resolution in zones with abrupt changes. The present work proposes an adaptive meshing methodology in order to adapt to these changing requirements without incrementing too much the number of parameters of the approximator. The proposal is based on simplicial meshes and Bellman error, with a criteria to add and remove points from the mesh: modifications to proposals in earlier literature including the volume of the affected simplices are proposed, alongside with methods to manipulate the mesh triangulation.